Implementation of Early Childhood Mathematics Learning Using Educational Game Tools at Abdi Pertiwi Kindergarten, Serang City District: Nurul Fatimah - nurul fatimah (Universitas muhammadiyah Banjarmasin, 2022)
This paper aims to discuss the implementation of learning, assessment and educational game tools in the concept of mathematical numbers that must be applied to early childhood according to the level of child development. This writing discusses the importance of learning mathematics and how the implementation and assessment of mathematics is applied through educational game tools, so that it can build mathematical thinking skills in children. One of them is by applying the constructivism learning method where children are encouraged to develop their cognitive abilities through educational game tools in the process of learning mathematics at school. This research method was carried out through descriptive research and conducted interviews with two teacher resource persons who teach at Abdi Pertiwi Kindergarten. The implementation of early childhood mathematics learning at Abdi Pertiwi Kindergarten is very necessary for educational game tools that can stimulate cognitive development and other developments according to the level of early childhood development. In addition, mathematics educational game tools must pay attention to children's interest in participating in learning at school